Bamboos Diversity in Banggai Kepulauan, Central Sulawesi, Indonesia - Damayanto, I Putu Gede P.; Rahmawati, Kusuma (Jurnal Biodjati, 2020)
A bamboo inventory for Banggai Kepulauan has never been done. Knowledge of the islands’ floristic diversity is poor. This study explored bamboo diversity in Banggai Kepulauan, Central Sulawesi, Indonesia. We conducted fieldwork from June – July 2019 on the islands of Peleng and Bakalan. Bamboo specimens were collected and deposited in Herbarium Bogoriense. We describe these specimens here. We found eight species: Bambusa tuldoides Munro, B. vulgaris Schrad. ex Wendl., Dendrocalamus asper (Schult.f.) Backer ex Heyne, Gigantochloa atter (Hassk.) Kurz, Neololeba atra (Lindl.) Widjaja, Schizostachyum brachycladum (Kurz ex Munro) Kurz, S. lima (Blanco) Merr., and Thyrsostachys siamensis Gamble. Here we record information on morphology, habitat and distribution alongside photographs and an identification key to the bamboo species of Banggai Kepulauan.